Species survival and evolutionary stability in sustainable habitats: The concept of ecological stability - Robert J. Aumann; Werner Güth (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
Whoever exists belongs to a species, which did not become extinct, has a (geno-) type, which should be well adjusted, and lives in a habitat which has been sustainable for a long time. To capture the first aspect we allow for interspecies competition and analyze the conditions for species survival. The second aspect refers to success in intraspecies competition of (geno-) types as in evolutionary biology and game theory. Survival in inter- and intraspecies competition together with sustainability define ecological stability, a concept which we illustrate by an example of solitary and social grazers who compete for food supply and who are endangered by the same predators. Although our approach is inspired by empirical evidence, no systematic attempt is made to apply it to some specific ecology.
urn:nbn:de:kobv:11-10060093
Keywords: 330